2020
DOI: 10.1159/000512429
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness and Safety of Childhood Growth Hormone Treatment in Noonan Syndrome

Abstract: <b><i>Introduction:</i></b> Few data exist on long-term growth hormone (GH) treatment in patients with Noonan syndrome (NS). <b><i>Objective:</i></b> To evaluate the effectiveness and safety of GH treatment in NS in clinical practice. <b><i>Methods:</i></b> Height gain, near-adult height (NAH), and safety were assessed in 2 complementary non-interventional studies: NordiNet® IOS and ANSWER. The safety analysis included 412 patients, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…This analysis assessed the impact of PTPN11 mutation status on long-term effectiveness outcomes in NS patients treated with rhGH. The effectiveness of GHT in treating short stature due to NS has been previously demonstrated (8,29,30,31,32,33,34). The impact of PTPN11 mutation status on long-term GHT response has previously been discussed, but additional studies are needed to further clarify the role of the different RAS/MAPK pathway aberrations in growth and in GH responsiveness.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This analysis assessed the impact of PTPN11 mutation status on long-term effectiveness outcomes in NS patients treated with rhGH. The effectiveness of GHT in treating short stature due to NS has been previously demonstrated (8,29,30,31,32,33,34). The impact of PTPN11 mutation status on long-term GHT response has previously been discussed, but additional studies are needed to further clarify the role of the different RAS/MAPK pathway aberrations in growth and in GH responsiveness.…”
Section: Discussionmentioning
confidence: 94%
“…HSDS (general population reference) was calculated using CDC national reference growth charts (27) for the ANSWER program® and using Japanese national reference data for the GHLIQUID-4020 trial (26). HSDS (NS-specific) was calculated using reference data reported by Ranke et al (28) for the ANSWER program® and using data reported by Isojima et al (29) for the GHLIQUID-4020 trial.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies that have reported long-term results on the efficacy of rhGH treatment in NS (34)(35)(36). Recently, in two complementary non-interventional studies, NordiNet ® IOS and ANSWER, it has been demonstrated that NS children treated with rhGH achieved significant height gain during the first 3 years of follow-up (37).…”
Section: Discussionmentioning
confidence: 99%
“…While in children with biallelic IGFALS variants, rhGH and rhIGF appear ineffective, preliminary reports have suggested that rhGH could be effective to accelerate growth velocity in children who are heterozygous carriers of IGFALS variants [164, 189]. rhGH is registered for the treatment of Noonan syndrome, based on the moderate effect on height velocity and adult height [190]. The growth response to rhGH treatment in children with 3M syndrome is variable and modest [185].…”
Section: Conditions With Decreased Gh Sensitivitymentioning
confidence: 99%